Analysis of speed run technique through biomechanics - Tomozei, R.-A.; Tanasa, R.-A.; Gavriluc, G.; Moraru, C. E. (Gymnasium - Scientific Journal of Education, Sports and Health, 2020)
The purpose of this study is to conduct a biomechanical analysis of speed run using the Simi Reality Motion Systems technology applied on two subjects, the fastest runners in the world in the 100 meter dash event. The biomechanical analysis focused on the most important characteristics of the evaluation of speed running: the start, first and second step and the maximum speed reached. Following the analysis of the start of the race, there were significantly relevant values registered at the knee joint of the lower limbs with a positive result in the U.B athlete. At the 40 meter line, the two subjects have a step length value of 2.67 m with a step frequency of 4.49m/s and 42.59 km/h. In conclusion, we believe that this study, using the Simi Motion system, provides us concrete data regarding the ideal way of approaching speed running biomechanics.